Translation and validation of the Indonesian version of Richard Campbell Sleep Questionnaire (RCSQ) in intensive care unit patients - Nunung Nurhayati; Agung Waluyo; I Made Kariasa; Sali Rahadi Asih; Hening Pujasari; Bahrul Hayat (School of Health Sciences Al-Ma'arif, 2026)
Background: Sleep quality is a critical determinant of recovery outcomes among patients admitted to intensive care units (ICUs); however, accurate sleep assessment remains challenging due to environmental disturbances and intensive medical interventions. The Richards–Campbell Sleep Questionnaire (RCSQ) is widely used to assess subjective sleep quality, yet evidence regarding its psychometric performance in Indonesian ICU settings remains limited. Objective: The purpose of this study was to evaluate the validity and reliability of RCSQ in the ICU and assess the extent to which this instrument can accurately reflect the patient's sleep experience in the ICU. Methods: A methodological cross-sectional study was conducted involving 11 adult ICU patients recruited using a total sampling technique. Data were collected between April and May 2025 using the Indonesian version of the RCSQ. Construct validity was assessed using item–total correlation analysis, while internal consistency was evaluated using Cronbach’s alpha coefficient. Descriptive statistics were used to summarize participants’ demographic characteristics. Results: All RCSQ items demonstrated satisfactory construct validity, with item–total correlation coefficients exceeding the critical r-value (r > 0.521) and statistical significance at p < 0.05. The instrument showed good internal consistency, with a Cronbach’s alpha value of 0.810, indicating reliable measurement of subjective sleep quality among ICU patients. Conclusion: The Indonesian version of the Richards–Campbell Sleep Questionnaire demonstrates acceptable validity and reliability for assessing subjective sleep quality in ICU patients. Nevertheless, further studies with larger and more diverse samples are recommended to confirm its robustness and to explore integration with objective sleep assessment methods in intensive care settings.